The Spatial Distribution of Creative Industries and Cultural Heritage in The Netherlands - Karima Kourtit; Jan Möhlmann; Peter Nijkamp; Jan Rouwendal (Tinbergen Institute, 2013)
This paper aims to investigate whether the spatial pattern of creative industries in the Netherlands has a relationship with the presence of cultural heritage or, in a more general sense, cultural capital. It first shows how the creative sector developed between 1994 2009 in relation to other Dutch sectors. Additionally, it analyses the urban dimension of the creative industry by focussing on the four large urban agglomerations in the Netherlands. And finally, it addresses the question whether a relationship exists between the share of the creative industry and the stock of cultural heritage at the level of municipalities. The paper concludes that local cultural heritage provides a statistically significant contribution to the presence of the creative industry at a municipality level.
Keywords: R1; R12; 330; creative industries; cultural heritage; cultural industry